Intellectual capital research opportunities on the sustainable growth of the MSME Industry in Indonesia - Ni Nengah Seri Ekayani; Ida Bagus Anom Purbawangsa; Luh Gede Sri Artini; Henny Rahyuda (Universitas Warmadewa, 2024)
The purpose of this paper is to briefly review the literature on intellectual capital and sustainability growth in manufacturing companies, service companies or other industries and propose research opportunities related to the role of intellectual capital in influencing sustainable growth in the Micro, Small and Medium Enterprises (MSME) industry. Two steps are involved in developing a research proposition. First, identify the characteristics of the contingent faced by each type of business. Second, match the characteristics of the contingent for each type of company with the appropriate intellectual capital based on the results of previous research. The contingent characteristics of the type of MSME business can be identified as innovation, management knowledge, competence, competitive advantage, and technological ability to be able to demonstrate sustainable growth of a business. These variables can be used and combined to improve managerial performance as the basis for sustainable growth of a business. From the various problems experienced by MSMEs, it is deemed necessary to raise the issue of the influence of intellectual capital on sustainability growth with a combination of these variables.